Activity Test of Water Hyacinth (Eichhornia crassipes) Leaf Extract Against Streptozotocin-Nicotinamide-Induced Diabetic Nephropathy in Rats - Afandi, Mukhamad; Herdwiani, Wiwin; Wijayanti, Tri (Universitas Airlangga, 2026)
Background: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. Chronic hyperglycemia in diabetes causes microvascular complications such as diabetic nephropathy (DN) which can affect kidney function. The parameters of kidney damage due to diabetes are increased levels of albumin and creatinine. Objective: The aim of this study was to determine the effect and effective dose of water hyacinth (Eichhornia crassipes) leaf extract on reducing blood glucose levels, microalbumin, serum creatinine, and improving kidney histopathology in STZ-NA-induced diabetic nephropathy rats. Method: The water hyacinth leaves were dried and made into a fine powder, then extracted using the maceration method using 70% ethanol. The initial testing process prepared 25 rats which were divided into 5 treatment groups, namely the negative group, positive control (Pioglitazone), water hyacinth leaf extract 61.25 mg/kg BW, 122.5 mg/kg BW and 245 mg/kg BW. The test animals were conditioned to be diabetic by being induced by STZ-Na intraperitoneally. Data analysis using One Way Anova and continued testing post hoc test. Results: The results showed that water hyacinth leaf extract at a dose of 245 mg/kg BW was the most effective in reducing microalbumin levels by 19.23% and improving kidney function, and had the potential to reduce blood glucose levels by 11.76% and serum creatinine by 15.04%, although it had not achieved the same effectiveness as the positive control. Conclusion: Water hyacinth leaf extract at a dose of 245 mg/kg BW can reduce blood glucose and microalbumin levels, as well as improve kidney function in diabetic nephropathy rats induced by STZ-Na.